THE IMPORTANCE OF THE PEDAGOGICAL COORDINATOR AT SCHOOL - Sabrina Trindade Pereira , Ellen; Andressa Daniel Paixão, Geovane; da Silva, Elitânia; Antônia da Silva Mendes, Maria; Amaral Ramos, Clemilde (Revista Gênero e Interdisciplinaridade, 2024)
This present work aims to elaborate a work on the importance of the pedagogical coordinator in schools, analyzing its contribution to the development of an objective and effective pedagogical practice. The method used is the bibliographic, surveyed in books by authors specialized in the subject. The pedagogical coordinator has as its main need to have knowledge in the area, with an uninterrupted formation, which makes it possible to precisely develop its professional attributions within the institution, the main one being interaction and action with the teachers. The main relevance of participatory planning is that the work will take place together with the coordinator collectively, building reflective and mutable planning as needed, reinforcing that for an institution to have good quality results the integration of all is required. For the coordinator needs to rescue his identity to raise awareness of his true attributions, so that he does a success and quality work in school institutions.